THE ROLE OF ARTIFICIAL INTELLIGENCE (AI) TECHNOLOGY IN THE DEVELOPMENT OF E-COMMERCE IN UZBEKISTAN (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This article investigates the development of e-commerce in Uzbekistan through the lens of artificial intelligence (AI) technologies. The study analyzes the scientific foundations and the growing importance of AI in online trade, focusing on its application in data processing, consumer behavior analysis, sales process optimization, and personalized marketing strategies. Using empirical data from Uzbek e-commerce platforms, the research examines AI-driven demand forecasting, dynamic pricing policies, automation, and customer service enhancement. The results show that the implementation of AI technologies significantly improves sales efficiency, customer satisfaction, and decision-making accuracy. The article also identifies key challenges such as data quality issues, shortage of qualified personnel, high implementation costs, and insufficient legal and ethical regulations. Based on these findings, the study outlines the stages, problems, and prospects of AI integration in Uzbekistan’s e-commerce system.
Keywords: Artificial intelligence; e-commerce; digital economy; online trading platforms; data analysis; personalized marketing; demand forecast; digital technologies; the economy of Uzbekistan